H.M. Naqvi’s Home Boy: A Socio-Cultural Conflict Analysis in the Context of Disruption and Multiculturalism - Aziz, Sardar Khawar; Nadeem, Farrukh (Pakistan Journal of Humanities and Social Sciences, 2024)
Through the lens of multiculturalism, this inquiry examines Home Boy by H.M. Naqvi. In particular, this study will look at how the selected literary work portrays several types of socio-cultural conflict that make it hard for the protagonists to blend in with their new communities. Concerns about intergroup tensions are at the forefront of multicultural communities' minds. According to this research, "socio-cultural conflict" describes when two or more cultures clash in areas such as politics, economics, religion, and society. The current study focuses on the book in question as an example of the socio-cultural conflict that might arise in heterogeneous society. Summing up the current human condition and the difficulties people face in a diverse city like New York is offered here. Characters in that society suffer as a result of these tensions as a result of immigration struggles, terrorist attacks, and identity issues. Cultural priorities, as shown in the book, lead to the denial of rights to many people in heterogeneous societies. Terrorist attacks and other forms of discrimination against them serve to solidify their inferiority complex. The facts on the hardships experienced by people in New York's postcolonial multicultural society are unearthed via the use of qualitative content analysis. Home Boy faces a plethora of socio-cultural conflicts and shows an interest in the real-life situations of the people living in such civilizations, according to the study. Their socioeconomic position is deteriorated by the prevailing culture, and H. M. Naqvi has communicated this misery via this work.